The spatial lag effects of bed load transport under unsteady flow conditions - Arie Setiadi Moerwanto (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2010)
The recent rapid development on the computation speed and capacity of random access memory of personal computer has presented opportunities and challenges on the implementation of finite element method on the modelling of river morphology response under steady as well as unsteady flow conditions. As consequences, the temporal and spatial lag effects due to sudden changes in hydrodynamic conditions as well as the requirement to take numerical space steps that are shorter than the adaptation length of the alluvial system to adjust to the changes in hydrodynamic conditions must be well taken into account. This paper describes in detail the modelling method including testing of model performance in simulating particularly the spatial lag of alluvial system.